In situ aqueous synthesis of genetically engineered polypeptide-capped Ag2S quantum dots for second near-infrared fluorescence/photoacoustic imaging and photothermal therapy. Issue 15 (15th March 2019) - Zhao, Dong-Hui; Yang, Xiao-Quan; Hou, Xiao-Lin; Xuan, Yang; Song, Xian-Lin; Zhao, Yuan-Di; Chen, Wei; Wang, Qiong; Liu, Bo
Abstract : Polypeptide-engineering capped silver sulfide quantum dots were prepared and used for second near-infrared fluorescence and photoacoustic imaging, and the photothermal therapy of tumors. Abstract : Ag2 S quantum dots have received extensive attention as theranostic agents for second near-infrared (NIR-II) fluorescence and photoacoustic dual-mode imaging, and photothermal therapy. However, it is still greatly challenging to synthesize Ag2 S quantum dots using aqueous synthesis. In this study, genetically engineered polypeptide-capped Ag2 S quantum dots were successfully synthesized. Three cysteines were integrated to the C-terminal and N-terminal of RGDPC10 A to enhance the stability and brightness of the synthesized Ag2 S quantum dots. The RGDPC10 A-capped Ag2 S quantum dots exhibited excellent stability, outstanding resistance to photobleaching, and a superior quantum yield of up to 3.78% in the NIR-II biological window. The in vitro and in vivo results showed that the RGDPC10 A-capped Ag2 S quantum dots possessed typical NIR-II fluorescence, photoacoustic imaging, and photothermal therapeutic effectiveness against tumors. Moreover, the results of toxicity assays suggested that the RGDPC10 A-capped Ag2 S quantum dots have negligible long-term toxicity. These findings open up the possibility for synthesizing theranostic agents by using this aqueous method.